Students' entrepreneurial regulation and intention to become an entrepreneur: a comparison between public and private universities - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh (Association for Professional Managers in South Africa, 2013)
Motivation and ability to orient ones' knowledge, thought and behavior to accomplish entrepreneurial goals and tasks has recently termed as entrepreneurial regulation. Entrepreneurial regulation strongly affects the whole process of new venture creation and specifically entrepreneurial opportunity exploration that is the first step in the entrepreneurship process. However, few researchers examined the construct particularly among potential entrepreneurs such as university students. This study aims to measure self-regulation (promotion focus), entrepreneurial self-efficacy and intention to become an entrepreneur among university students. 722 students from both public and private universities were randomly selected as the participants based on the assumption that entrepreneurship education and training programs and university environment highly influence the development of entrepreneurial regulation, self-efficacy and intention in students. Analysis of the data revealed a significant relationship between students' promotion focus, entrepreneurial self-efficacy and entrepreneurial intentions. Furthermore, students from public universities had significantly higher entrepreneurial regulation and intentions than their counterparts from private universities. We discuss the implications of the findings for entrepreneurship research, theory development and education.